2022
DOI: 10.1002/jpen.2280
|View full text |Cite
|
Sign up to set email alerts
|

Stability of glutathione added as a supplement to parenteral nutrition

Abstract: Background: Most very premature newborns (<32 weeks of gestation) receive parenteral nutrition (PN) that is inherently contaminated with peroxides. Oxidative stress induced by PN is associated with bronchopulmonary dysplasia, a main pathological complication in these infants who have weak antioxidant capacity to detoxify peroxides because of their glutathione deficiency. In animals, glutathione supplementation of PN prevented oxidative stress and alveolar loss (the main characteristic of bronchopulmonary dyspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…GSSG was used rather than GSH due to its improved stability in PN [ 15 ] and similar affinity for γ-glutamyl transferase [ 16 ]. A recent article [ 17 ] demonstrated that the loss of GSSG in PN is caused by the presence of cysteine in PN. The reaction leads to the generation of a mixed disulfide cysteine–glutathione.…”
Section: Methodsmentioning
confidence: 99%
“…GSSG was used rather than GSH due to its improved stability in PN [ 15 ] and similar affinity for γ-glutamyl transferase [ 16 ]. A recent article [ 17 ] demonstrated that the loss of GSSG in PN is caused by the presence of cysteine in PN. The reaction leads to the generation of a mixed disulfide cysteine–glutathione.…”
Section: Methodsmentioning
confidence: 99%
“…Whatever the mechanism, the fact that GSSG supplementation prevents Gpx1 hypermethylation is important. Indeed, GSSG supplementation is proposed for premature newborns who require PN [ 8 , 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both GSSG and GSH are substrates for the gamma-glutamyl cycle, which promotes the intracellular transfer of cysteine from plasma glutathione (GSH or GSSG) with a view to the new cellular synthesis of glutathione [ 25 ]. GSSG is chosen because of its better stability in PN solutions than GSH [ 26 ]. In vivo, glutathione supplementation helps maintain optimal GPx activity to detoxify PN peroxides as they arrive.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted supplementation with GSH, for example, as the principal antioxidant for premature infants with antioxidant deficiencies, is being investigated in literature for its therapeutic and preventative potential. Mode of supplementation is also imperative as GSH addition to nutritional modalities such as parenteral nutrition or infant formula has the potential for oxidation of the antioxidant leading to decreased availability [37].…”
Section: Discussionmentioning
confidence: 99%